2017
DOI: 10.1007/s40328-017-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of the PCA/EOF method for the analysis and modelling of temporal variations of geoid heights over Poland

Abstract: Temporal variations of geoid heights are vitally important in geodesy and Earth science. They are essentially needed for dynamic and kinematic updates of the static geoid model. These temporal variations, which substantially differ for different geographic locations, can successfully be determined using the Gravity Recovery And Climate Experiment (GRACE) mission data. So far, statistical decomposition methods, e.g. the Principal Component Analysis/Empirical Orthogonal Function (PCA/EOF) method, have not been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The Principal Component Analysis/Empirical Orthogonal Function (PCA/EOF) method was applied for both, analysis and modelling temporal variations of geoid heights (Godah et al, 2018c). It was shown that the use of the first PCA mode and EOF loading pattern allows to obtain a large signal of temporal variations of geoid heights over the area of Poland (96.3%, in terms of total variance) while with the first three PCA modes and EOF loading patterns ~99.93% of total variance of temporal variations of geoid heights can be obtained.…”
Section: Temporal Variations Of the Gravity Field From Grace Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The Principal Component Analysis/Empirical Orthogonal Function (PCA/EOF) method was applied for both, analysis and modelling temporal variations of geoid heights (Godah et al, 2018c). It was shown that the use of the first PCA mode and EOF loading pattern allows to obtain a large signal of temporal variations of geoid heights over the area of Poland (96.3%, in terms of total variance) while with the first three PCA modes and EOF loading patterns ~99.93% of total variance of temporal variations of geoid heights can be obtained.…”
Section: Temporal Variations Of the Gravity Field From Grace Datamentioning
confidence: 99%
“…They were analysed and modelled using two methods: SD method and the PCA/EOF method (Godah et al, 2018b). In the area investigated PCA/EOF method provides slightly better results compared to the Fourier analysis and SD methods (Godah et al, 2018c).…”
Section: Temporal Variations Of the Gravity Field From Grace Datamentioning
confidence: 99%
“…From the past to the present, researchers have calculated many parameters such as local or global geoid models, gravity anomalies (free-air and Bouguer), and gravity disturbances for different regions of the earth by using GGMs. As a result of these calculations, many different methods and approaches have been put forward [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, e.g. Rangelova (2007), Rangelova and Sideris (2008), Rangelova et al (2010), Krynski et al (2014) and Godah et al (2017Godah et al ( , 2018, reveled the importance of temporal variations of geoid heights for high accuracy regional geoid modelling that has been considered as one of the activities of the Joint Study Group 0.15 (JSG 0.15) of the Commission 2 -Gravity Field of the International Association of Geodesy (IAG) (see Drewes et al 2016).…”
Section: Introductionmentioning
confidence: 99%